Teaching About Values and Goals: Applications of the Circumplex Model to Motivation, Well-Being, and Prosocial Behavior. (October 2014) - Kasser, Tim
In this article, I review how people organize values and goals in their minds and I suggest teaching demonstrations, exercises, and assignments to help students learn this material. I pay special attention to circumplex models, which represent the extent of conflict or compatibility between values and goals, and to the well-researched distinction between intrinsic (e.g., self-acceptance and community feeling) and extrinsic (e.g., financial success and image) goals. I also provide a brief overview of the literature regarding how both a dispositional focus on goals and the momentary activation of goals relate to people's personal well-being and to their prosocial and proenvironmental attitudes and behavior. Finally, I discuss implications for students' experiences with advertising messages in their day-to-day lives.